Pelatihan Budidaya Sayur dengan Metode Hidroponik di Desa Guntung Payung, Banjarbaru - Sunardi Sunardi; Wiwin Tyas Istikowati; Eny Dwi Pujawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Guntung Payung land condition majority is peat that makes low productivity of vegetables, difficult land preparation, and much consume of fertilizer. In the other hand, partner location in this program is an urban area that near international airport, caused the change in land function from the farming area to be residence area. That condition caused the traditional farming area is not enough. The low education level and skills of community inhibit to learn and try new technology for increasing income level. The training of the hydroponic system to the community in this program can solve the problem that happens in this partner community. With knowledge of hydroponic technology, it is expected that the partner’s income will increase and this group of hydroponic farmers can supply the vegetables need in Banjarbaru area.